Nano-boron composite magnesium-based hydrogen storage material and preparation method thereof

By preparing nanoboro composite magnesium-based hydrogen storage materials, using boron and magnesium in nano-scale structures to recombine, the problem of low mass efficiency of magnesium-based hydrogen storage alloys is solved, significantly improving the hydrogen absorption and dehydrogenation speed, and optimizing hydrogen storage conditions.

CN119710402AActive Publication Date: 2025-03-28KUNMING UNIV OF SCI & TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411890623.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing magnesium-based hydrogen storage alloy has low mass efficiency and slow hydrogen absorption and dehydrogenation speeds, which limits its application in hydrogen storage materials.

Method used

By preparing nanoboro composite magnesium-based hydrogen storage materials, the nano-scale structure formed by the nano-scale structure composite and magnesium, and boron atoms aggregation are used as the intermediate medium for the hydrogen absorption and hydrogen release process, the microstructure of magnesium-based hydrogen storage materials is improved, the activity of magnesium is enhanced, and the rate of hydrogen absorption and dehydrogenation is improved.

Benefits of technology

The hydrogen absorption and dehydrogenation speed of magnesium-based hydrogen storage materials is significantly improved, and the hydrogen storage conditions are optimized, so that the material has better hydrogen storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710402A_ABST
    Figure CN119710402A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-boron composite magnesium-based hydrogen storage material and a preparation method thereof, and belongs to the technical field of preparation and development of new energy materials. The nano-boron composite magnesium-based hydrogen storage material comprises the following components in percentage by mass: 1-30% of boron and the balance of magnesium, and boron atoms are gathered into boron nano-structures (nanotubes, nanosheets, nanohorns and nanospheres) in a smelting process and are partially embedded into magnesium, so that diffusion of hydrogen and magnesium is enhanced. According to the magnesium-based hydrogen storage material, an intermediate medium is provided for the magnesium-based hydrogen storage material in the hydrogen absorption and hydrogen desorption process through a nano boron structure (nanotubes, nanosheets, nanohorns and nanospheres), and the hydrogen storage conditions of the magnesium-based hydrogen storage material are effectively optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation and development of new energy materials, and relates to a nano-boron composite magnesium-based hydrogen storage material and a preparation method thereof. Background Art

[0002] Hydrogen storage materials are one of the key technologies for realizing hydrogen energy applications. They can store and release hydrogen, which is crucial for the transportation and storage of hydrogen energy. The application of hydrogen storage materials is mainly concentrated in the fields of fuel cells, distributed energy supply, new energy vehicles, etc. Existing types of hydrogen storage materials include physical adsorption hydrogen storage materials, metal hydride-based hydrogen storage alloys, organic liquid hydrogen storage materials, liquid ammonia hydrogen storage materials, and coordination hydrides. Metal hydride-based hydrogen storage is currently the most promising and fastest-growing solid-state hydrogen storage method. It has the characteristics of high hydrogen storage volume density, easy operation, convenient transportation, low cost, good safety, and good reversible cycle. However, the quality efficiency of metal hydride-based hydrogen storage alloys is relatively low.

[0003] Magnesium-based hydrogen storage materials are considered to be a very promising solid-state hydrogen storage material due to their high theoretical weight hydrogen storage density and volume hydrogen storage density, as well as the abundance and low cost of magnesium resources. The cubic structure of Mg2Ni has a theoretical hydrogen storage capacity of 3.6wt%, and is the earliest magnesium-based hydrogen storage material studied. Mg2Ni undergoes a hydrogen absorption reaction at 300°C and 2MPa to form the corresponding hydride Mg2NiH4. As a hydrogen storage material, MgH2 has a theoretical hydrogen storage capacity of 7.6wt%, which is higher than that of Mg2Ni material and meets the goal of mobile hydrogen storage, but its poor kinetic properties hinder its practical application. Therefore, it is of great significance to improve the hydrogen absorption and dehydrogenation rates of magnesium-based hydrogen storage alloys so that magnesium-based hydrogen storage materials have better hydrogen storage conditions.

[0004] Therefore, it is necessary to provide a nano-boron composite magnesium-based hydrogen storage material and a preparation method thereof, optimize the hydrogen storage conditions of the magnesium-based hydrogen storage material, and enable the magnesium-based hydrogen storage material to achieve better hydrogen storage conditions. Summary of the invention

[0005] In order to overcome the problems in the background technology, the present invention prepares a nano-boron composite magnesium-based hydrogen storage material, so that boron is composited with magnesium in a nanoscale structure (nanotubes, nanosheets, nanohorns, nanospheres). The nanoscale structure formed by the aggregation of boron atoms can improve the internal microstructure of the composite magnesium-based hydrogen storage material, enhance the activity of magnesium, and can serve as an intermediate medium connecting magnesium with the outside world. Hydrogen atoms can diffuse into magnesium through the boron nanostructure, thereby enhancing the hydrogen absorption and desorption rate of the magnesium-based hydrogen storage material, so that the magnesium-based hydrogen storage material has better hydrogen storage conditions.

[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0007] On one hand, the present invention provides a nano-boron composite magnesium-based hydrogen storage material, wherein the nano-boron composite magnesium-based hydrogen storage material comprises, by mass fraction, 1-30% boron and the remainder magnesium. In the nano-boron composite magnesium-based hydrogen storage material, boron atoms are aggregated into a nano-scale structure and composited with magnesium, and the nano-boron serves as an intermediate medium in the process of hydrogen absorption and desorption.

[0008] Another aspect of the present invention provides a method for preparing the above hydrogen storage material, the preparation method comprising the following steps:

[0009] (1) smelting weighed magnesium powder and magnesium diboride powder, introducing a protective gas during the smelting process, adding a refining agent to the melt, and obtaining a smelted body after the melt is cooled;

[0010] (2) crushing the smelt obtained in step (1) into fragments, and ball-milling the fragments in a non-oxidizing atmosphere or a vacuum environment to obtain a nano-boron composite magnesium-based hydrogen storage material.

[0011] Preferably, in step (1), the smelting temperature is 700-1500° C. and the holding time is 1-5 h.

[0012] Preferably, in step (1), the refining agent is a mixture of KCl, MgCl2, and CaF2, and the mass of the refining agent added is 2% of the total mass of magnesium powder and magnesium diboride. The refining agent used in the magnesium alloy refining process can be used as the refining agent of the present invention.

[0013] Preferably, in the step (1), when the smelting temperature rises to 350°C, the shielding gas is introduced, and during the cooling process, when the temperature drops to 350°C, the shielding gas is stopped, and the shielding gas introduction flow rate is 3-6 L / h.

[0014] Preferably, in step (1), the protective gas is one of argon and carbon dioxide or a mixed gas of argon and carbon dioxide, and in the mixed gas, the volume ratio of carbon dioxide to argon is CO2:Ar=8:2.

[0015] Preferably, in step (2), the ball-to-material ratio is 20-120:1, the ball-milling speed is 300-900 rpm, and the ball-milling time is 12-60 h.

[0016] Preferably, in step (2), the ball milling process is carried out in a cycle of ball milling for 30 minutes and resting for 20 minutes.

[0017] Preferably, before smelting the magnesium powder and magnesium diboride powder, the smelting equipment is preheated to 150-250°C.

[0018] Preferably, in step (2), the non-oxidizing atmosphere is argon.

[0019] Beneficial effects of the present invention:

[0020] 1. The present invention prepares a nano-boron composite magnesium-based hydrogen storage material containing nano-scale structures (nanotubes, nanosheets, nanohorns, nanospheres), improves the internal microstructure of the magnesium-based hydrogen storage material, and uses the boron nanostructure as an intermediate medium in the hydrogen absorption and desorption process, thereby effectively improving the hydrogen absorption and dehydrogenation speed of the magnesium-based hydrogen storage material, thereby optimizing the hydrogen storage effect of the magnesium-based hydrogen storage material.

[0021] 2. The preparation process of the present invention is pollution-free, does not produce toxic substances, and the process is simple and easy to implement, with low preparation cost, and is suitable for industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a schematic diagram of the process for preparing the nano-boron composite magnesium-based hydrogen storage material of the present invention;

[0023] Figure 2 It is a microstructure schematic diagram of the simulated hydrogen absorption process of the nano-boron composite magnesium-based hydrogen storage material of the present invention.

[0024] Figure 3 It is a schematic diagram of the microstructure of the nano-boron composite magnesium-based hydrogen storage material of the present invention in the simulated hydrogen release process. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below in conjunction with specific embodiments.

[0026] In the examples of the present invention, all chemical reagents not specified were commercially available analytically pure for the experiments.

[0027] Example 1

[0028] This example prepares a nano-boron composite magnesium-based hydrogen storage material according to the following method:

[0029] (1) In a glove box filled with Ar gas, 68 g of magnesium powder and 32 g of magnesium diboride alloy powder were weighed, with a total of 100 g, of which the mass percentage of boron was 15%, and 2 g of a refining agent was weighed;

[0030] (2) First, place the crucible into a melting furnace, heat it to 150°C, and preheat it for 30 minutes. Then, weigh the magnesium powder and magnesium diboride into the crucible and continue to heat it. When the temperature in the furnace rises to 350°C, introduce a CO2-Ar mixed gas at a flow rate of 3.5L / h. In the mixed gas, the volume ratio of CO2 to Ar is 8:2. When the temperature rises to 900°C, add a refining agent, stir for 2 minutes, and keep warm for 1.5 hours. During this period, ventilation is continued. The ventilation volume can be appropriately increased during the stirring process.

[0031] (3) After the heat preservation is completed, the material is cooled, and ventilation is stopped when the temperature is 350°C, and the material is cooled to room temperature. The obtained block material is taken out, cut into small pieces, and put into a ball mill for ball milling. The ball milling process is carried out under an Ar gas atmosphere (Ar gas is introduced into the equipment before ball milling to exhaust the air in the equipment and create an Ar gas environment), the ball-to-material ratio is 70:1, the ball milling speed is 800rpm, and the ball milling time is 30h. After the ball milling is completed, the material is cooled, and the powder is taken out to obtain a nano-boron composite magnesium-based hydrogen storage material. In the nano-boron composite magnesium-based hydrogen storage material prepared in this embodiment, boron atoms are aggregated into a nanotube structure.

[0032] The microstructure diagram of the hydrogen absorption process of the nano-boron composite magnesium-based hydrogen storage material prepared in this embodiment is obtained by first-principles simulation calculation as shown in Figure 2 As shown, the white atoms are hydrogen, the black atoms are boron, and the gray atoms are magnesium. Figure 2 It can be seen that boron itself can react with hydrogen, and the specific way in which boron nanotubes are composited with magnesium is to partially embed into magnesium, causing lattice distortion of magnesium and enhancing the activity of magnesium. The microstructure schematic diagram of the hydrogen release process of the nano-boron composite magnesium-based hydrogen storage material prepared in this embodiment is obtained by first-principles simulation calculation as shown in FIG. Figure 3 As shown, through Figure 3 It can be seen that magnesium atoms gather on the surface of boron nanotubes, and some hydrogen atoms are adsorbed around the boron nanotubes, indicating that boron nanotubes can promote the movement of magnesium and hydrogen atoms, thereby accelerating the rate of hydrogen absorption and desorption, and optimizing the hydrogen storage conditions of composite magnesium-based hydrogen storage materials.

[0033] Example 2

[0034] This example prepares a nano-boron composite magnesium-based hydrogen storage material according to the following method:

[0035] (1) In a glove box filled with Ar gas, 87 g of magnesium powder and 13 g of magnesium diboride alloy powder were weighed, with a total of 100 g, of which the mass percentage of boron was 6%, and 2 g of a refining agent was weighed;

[0036] (2) First, place the crucible into a melting furnace, heat it to 150°C, and preheat it for 30 minutes. Then, weigh the magnesium powder and magnesium diboride into the crucible and continue to heat it. When the temperature in the furnace rises to 350°C, introduce a CO2-Ar mixed gas at a flow rate of 4 L / h. In the mixed gas, the volume ratio of CO2 to Ar is 8:2. When the temperature rises to 800°C, add a refining agent, stir for 2 minutes, and keep warm for 2 hours. During this period, ventilation is continued. The ventilation volume can be appropriately increased during the stirring process.

[0037] (3) After the insulation is completed, the material is cooled, and ventilation is stopped when the temperature reaches 350°C. The material is cooled to room temperature, the block material is taken out, cut into small pieces, and put into a ball mill for ball milling. The ball milling process is carried out in an Ar gas atmosphere, with a ball-to-material ratio of 20:1, a ball milling speed of 800 rpm, and a ball milling time of 30 h. After the ball milling is completed, the material is cooled, and the powder is taken out to obtain a nano-boron composite magnesium-based hydrogen storage material.

[0038] The performance of the nano-boron composite magnesium-based hydrogen storage material prepared in this example is similar to that of the nano-boron composite magnesium-based hydrogen storage material in Example 1.

[0039] Example 3

[0040] This example prepares a nano-boron composite magnesium-based hydrogen storage material according to the following method:

[0041] (1) In a glove box filled with Ar gas, 97.8 g of magnesium powder and 2.2 g of magnesium diboride alloy powder were weighed, with a total amount of 100 g, of which the mass percentage of boron was 1%, and 2 g of a refining agent was weighed;

[0042] (2) First, place the crucible into a melting furnace, heat it to 250°C, preheat it for 30 minutes, then add the weighed magnesium powder and magnesium diboride into the crucible, continue to heat it, and when the temperature in the furnace rises to 350°C, introduce a CO2-Ar mixed gas at a flow rate of 3L / h. In the mixed gas, the volume ratio of CO2 to Ar is 8:2. When the temperature rises to 700°C, add a refining agent, stir for 2 minutes, and keep warm for 1 hour. During this period, ventilation is continued, and the ventilation volume can be appropriately increased during the stirring process;

[0043] (3) After the insulation is completed, the material is cooled, and ventilation is stopped when the temperature reaches 350°C. The material is cooled to room temperature, the block material is taken out, cut into small pieces, and put into a ball mill for ball milling. The ball milling process is carried out in an Ar gas atmosphere, with a ball-to-material ratio of 120:1, a ball milling speed of 300 rpm, and a ball milling time of 12 h. After the ball milling is completed, the material is cooled, and the powder is taken out to obtain a nano-boron composite magnesium-based hydrogen storage material.

[0044] The performance of the nano-boron composite magnesium-based hydrogen storage material prepared in this example is similar to that of the nano-boron composite magnesium-based hydrogen storage material in Example 1.

[0045] Example 4

[0046] This example prepares a nano-boron composite magnesium-based hydrogen storage material according to the following method:

[0047] (1) In a glove box filled with Ar gas, 36.3 g of magnesium powder and 63.7 g of magnesium diboride alloy powder were weighed, with a total of 100 g, of which the mass percentage of boron was 30%, and 2 g of a refining agent was weighed;

[0048] (2) First, place the crucible into a smelting furnace, heat it to 200°C, and preheat it for 30 minutes. Then, weigh the magnesium powder and magnesium diboride into the crucible and continue to heat it. When the temperature in the furnace rises to 350°C, introduce a CO2-Ar mixed gas at a flow rate of 6L / h. In the mixed gas, the volume ratio of CO2 to Ar is 8:2. When the temperature rises to 1500°C, add a refining agent, stir for 2 minutes, and keep warm for 5 hours. During this period, ventilation is continued. The ventilation volume can be appropriately increased during the stirring process.

[0049] (3) After the insulation is completed, the material is cooled, and ventilation is stopped when the temperature reaches 350°C. The material is cooled to room temperature, the block material is taken out, cut into small pieces, and put into a ball mill for ball milling. The ball milling process is carried out in a vacuum environment, the ball-to-material ratio is 80:1, the ball milling speed is 900 rpm, and the ball milling time is 60 h. After the ball milling is completed, the material is cooled, the powder is taken out, and a nano-boron composite magnesium-based hydrogen storage material is obtained.

[0050] The performance of the nano-boron composite magnesium-based hydrogen storage material prepared in this example is similar to that of the nano-boron composite magnesium-based hydrogen storage material in Example 1.

[0051] In summary, in the nano-boron composite magnesium-based hydrogen storage material prepared by the present invention, boron atoms can aggregate to form a nanoscale structure. The nanostructure formed by boron atoms can not only be partially embedded in magnesium to produce lattice distortion and enhance the activity of magnesium, but also serve as an intermediate medium to enable hydrogen atoms to diffuse into magnesium through nano-boron, thereby increasing the hydrogen absorption and release rate of the magnesium-based hydrogen storage material, so that the nano-boron composite magnesium-based hydrogen storage material has more excellent hydrogen storage conditions.

[0052] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A nano-boron composite magnesium-based hydrogen storage material, characterized in that: The nano-boron composite magnesium-based hydrogen storage material comprises, by mass fraction, 1-30% boron and the remainder magnesium. In the nano-boron composite magnesium-based hydrogen storage material, boron atoms are aggregated into a nano-scale structure and composited with magnesium, and the nano-boron serves as an intermediate medium in the process of hydrogen absorption and release.

2. The method for preparing a nano-boron composite magnesium-based hydrogen storage material according to claim 1, characterized in that: The preparation method comprises the following steps: (1) smelting weighed magnesium powder and magnesium diboride powder, introducing a protective gas during the smelting process, adding a refining agent to the melt, and obtaining a smelted body after the melt is cooled; (2) crushing the smelt obtained in step (1) into fragments, and ball milling the fragments in a non-oxidizing atmosphere or a vacuum environment to obtain a nano-boron composite magnesium-based hydrogen storage material.

3. The preparation method according to claim 2, characterized in that: In the step (1), the smelting temperature is 700-1500° C. and the holding time is 1-5 hours.

4. The preparation method according to claim 2, characterized in that: In the step (1), the refining agent is a mixture of KCl, MgCl2 and CaF2, and the mass of the refining agent added is 2% of the total mass of the magnesium powder and magnesium diboride.

5. The preparation method according to claim 2, characterized in that: In the step (1), when the smelting temperature rises to 350° C., the shielding gas is introduced. During the cooling process, when the temperature drops to 350° C., the shielding gas is stopped. The shielding gas introduction rate is 3-6 L / h.

6. The preparation method according to claim 2, characterized in that: In the step (1), the protective gas is one of argon and carbon dioxide or a mixed gas of argon and carbon dioxide. In the mixed gas, the volume ratio of carbon dioxide to argon is CO2:Ar=8:

2.

7. The preparation method according to claim 2, characterized in that: In the step (2), the ball-to-material ratio is 20-120:1, the ball-milling speed is 300-900 rpm, and the ball-milling time is 12-60 h.

8. The preparation method according to claim 2 or 7, characterized in that: In the step (2), the ball milling process is carried out in a cycle of ball milling for 30 minutes and resting for 20 minutes.

9. The preparation method according to any one of claims 2 to 7, characterized in that: Before smelting magnesium powder and magnesium diboride powder, preheat the smelting equipment to 150-250℃.

10. The preparation method according to claim 2, characterized in that: In the step (2), the non-oxidizing atmosphere is argon.

Citation Information

Patent Citations

  • High-performance nano magnesium-based hydrogen storage material and preparation method thereof

    CN105586519A

  • Magnesium-based composite hydrogen storage material and preparation method thereof

    CN110182758A

  • Preparation method of nano-particle magnesium-based composite hydrogen storage material

    CN115246627A

  • Magnesium-based composite hydrogen storage material as well as preparation method and application thereof

    CN118458691A

  • Magnesium and multi-wall nano carbon tube composite hydrogen storage material and process for preparing same

    CN1699611A